Perceived Competition, Leadership Effort, and Organizational Outreach in Religious Nonprofit Organizations - Scheitle, Christopher P. (Review of religious research, 2015)
The religious economies literature argues that religious leaders are motivated by the existence of competition. This motivation is said to lead to more effort and outreach on the part of leaders and their organizations. Previous research examining this hypothesis has focused on the presence of religious or organizational diversity at an ecological level. This study shifts the focus to leaders' perception of competition as the central mechanism of interest. Utilizing data produced from a survey of founders of religious nonprofit organizations, I analyze how perceived competition shapes the number of hours the leader puts into the organization and the number of outreach strategies the organization pursues. The analysis finds no support for the competition-effort hypothesis.